12-months of increased dietary intake does not exacerbate disordered eating-related attitudes, stress, or depressive symptoms in women with exercise-associated menstrual disturbances: The REFUEL randomized controlled trial. (June 2023) - Strock, Nicole C.A.; De Souza, Mary Jane; Mallinson, Rebecca J.; Olmsted, Marion; Allaway, Heather C.M.; O'Donnell, Emma; Plessow, Franziska; Williams, Nancy I.
Abstract: Disordered eating-related attitudes are a leading cause of energy deficiency and menstrual disturbances in exercising women. Although treatment recommendations include psychological counseling with increases in dietary intake, a key concern is whether increased dietary intake may exacerbate negative eating behaviors. Objective: To determine the effects of a 12-month nutritional intervention on eating-related attitudes and psychological characteristics in exercising women with oligomenorrhea/amenorrhea (Oligo/Amen). Methods: Intent-to-treat analysis of the REFUEL randomized controlled trial (#NCT00392873) in 113 exercising women (age [mean±SEM]:] 21.9 ± 0.4 yrs; BMI: 20.9 ± 0.2 kg/m 2 ). Women were randomized to increase energy intake 20–40% above baseline energy needs (Oligo/Amen+Cal, n = 40) or maintain energy intake (Oligo/Amen Control, n = 36) while maintaining their exercise behaviors. A reference group of ovulatory women (OVref, n = 37) maintained diet and exercise behaviors. Body composition, eating attitudes, stress, and depressive symptoms were assessed at baseline and every 3 months. Results: At baseline, the Oligo/Amen groups had higher drive for thinness, cognitive restraint, and eating disorder risk than OVref group (p < 0.001). Increased energy intake led to increases in percent body fat and fat mass (p < 0.010), but not psychobehavioral outcomes, in the Oligo/Amen+Cal compared to Oligo/Amen Control group. Independent of group, cognitive restraint decreased (p < 0.001) and resilient coping increased (p < 0.007) over 12-months, while perceived stress (p = 0.143) and depressive symptoms (p = 0.344) were unchanged. Discussion: Long-term nutritional intervention consisting of modest increases in dietary intake with guidance from a registered dietician and a psychologist increases body and fat mass without increasing disordered eating-related attitudes, stress, or depressive symptoms in exercising women with Oligo/Amen. Highlights: REFUEL: only randomized controlled trial and longest duration nutritional intervention in women with menstrual disturbances. Modest increase in energy intake was sufficient to result in improvements in body weight and fat mass. Increased energy intake did not worsen disordered eating-related attitudes, psychological stress, or depressive symptoms. Improved dietary cognitive restraint and resilient coping occurred regardless of intervention group. A multidisciplinary team, including a dietician and psychologist, yielded a positive impact on intent-to-treat participants.